EXPLAINING THE OBSTACLES TO THE DEVELOPMENT OF CIVIL SOCIETY - Faisal Hamidi, Ali Akbar Amini (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In recent decades, one of the socio-political terms and expressions that has been vastly regarded and applied by experts and thinkers in the relevant field is the term civil society. Since civil society plays a noteworthy and undeniable role in revitalizing public and citizen rights, different aspects of this subject and associated issues have been explored, including obstacles to the development of the society. Consequently, in the current research, it is tried to inspect the existing obstacles to the development of civil society. In this study, a descriptive-library technique has been utilized to collect information and data and an analytical technique has been applied to achieve the result.